Evaluation of Boiler Maintenance Using The Failure Mode and Effect Analysis Approach at KM. Tilongkabila - Laili, Qurrotul; Nugroho, Azis; Robbi, Shofa Dai; Kristiyono, Antonius Edy; Sianturi, Intan; SUTRISNO, IMAM (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Boilers experience frequent problems, such as scale formation, unstable steam pressure, incomplete combustion, and difficulty starting. Therefore, this study uses a quantitative method with the Failure Mode and Effect Analysis (FMEA) approach, which aims to determine maintenance and prevention to minimize these problems. This method determines the failure priority obtained from the Risk Priority Number (RPN) calculation based on assessment factors such as severity, frequency of occurrence, and the likelihood of failure being detected in each component. The results of these calculations indicate that the steam drum component falls into the highest category, with an RPN of 32. The other 12 components fall into the medium category: the feed water pump, electrode, photocell, nozzle, blower fan, solenoid valve, fuel pump, blowdown valve, main steam valve, scum valve, non-return valve, and gauge glass, with RPN values ranging from 12 to 24. Furthermore, the components in lowest category include the fuel filter, safety valve, and manometer, with RPN values ranging from 8 to 10. Therefore, the recommended improvements based on the FMEA results can be used as evaluation material to ensure the effectiveness of the improvements. Furthermore, regular boiler maintenance and monitoring are required, especially for components such as the steam drum, which requires additional routine maintenance schedules, repeated evaluations related to water treatment, and determining appropriate repairs for any steam drum failures.